Revolutionizing 3D electronics: Single-step femtosecond laser fabrication of conductive embedded structures and circuitry - Saurabh Awasthi; SeungYeon Kang (Materials Today Advances)
Recent advancements in 3D additive manufacturing and multilayer, multimaterial printing have highlighted their significant potential across a broad spectrum of applications. Despite progress in the fabrication of 3D structures from single materials or materials with similar properties, the fabrication of 3D embedded structures with intricate geometries—particularly those integrating metal components within a dielectric matrix—remains a formidable challenge. Traditional fabrication methods often require multiple pre- and post-processing steps, and achieving precise geometrical control for embedded components demands specialized techniques. In this paper, we introduce a pioneering approach that redefines 3D electronics fabrication through a single-step femtosecond direct laser writing (fs-DLW) technique. This is the first study to demonstrate the fabrication of conductive ''embedded'' metal wires through direct laser writing, enabling the integration of metal components directly within a dielectric matrix in a single processing step. We showcase the fabrication of conductive silver wires, two-dimensional planar patches, and three-dimensional embedded silver wire circuitry within a gelatin matrix. Using two-photon absorption (TPA) assisted photoreduction, this technique not only simplifies the fabrication process by eliminating the need for additional post-processing but also addresses the challenge of silver particle aggregation by precisely controlling the incident pulse rate. This work opens new avenues for the fabrication of complex, multifunctional devices and sensors, with applications spanning terahertz technology, optical metamaterials, plasmonics, flexible electronics, and beyond. It also extends to the development of innovative strategies for 3D packaging, thereby enhancing its potential impact. The ability to integrate conductive materials directly into 3D structures in a single-step process marks a significant advancement in the field of additive manufacturing, offering enhanced design flexibility and fabrication efficiency.